Kurdish language option in Google Translate - Ahmed, L.Dr. Muhammed Hussein (Sulaimani Journal for Humanities, 2025)
One of the great achievements for the Kurdish language in 2022, specifically on 11/5/2022, was its inclusion in the Google Translate network. Although it is constantly being improved, the quality of the translation, like that of all other languages in the network (which includes 133 languages, and with dialects, it becomes 249 languages), is not without issues and shortcomings—both in terms of vocabulary and grammar, as well as meaning and pragmatics. This is a normal phenomenon. On one hand, it is related to grammatical challenges and linguistic and cultural diversity, and on the other hand, it relates to machine translation itself, which is what Google Translate represents. In this study, after selecting two texts in the field of linguistics (such as samples/research examples), we have attempted to present the linguistic problems and shortcomings in English-Kurdish translation. Using quantitative data, the issues in each aspect (spelling, punctuation, vocabulary, dictionary, grammar) have been identified, examined, and analyzed. The results showed that the Kurdish language has achieved significant success in Google Translate (despite its relatively short existence), and many of the errors and problems can be corrected. Finally, recommendations and suggestions are provided to address the issues in English-Kurdish translation, which offers an outstanding service to the Kurdish language and its speakers and can keep pace with global technological and cultural development. This helps move toward the integration of words and idioms and the standardization of the Kurdish language.